Sprinters` and marathon runners` performances are better explained by muscle fibers` percentage cross-sectional area than any other parameter of muscle fiber composition - Methenitis, S.; Stasinaki, A.-N.; Mpampoulis, T.; Papadopoulos, C.; Papadimas, G.; Zaras, N.; Terzis, G. (Sports, 2025)
The present study aimed to investigate the correlation between muscle fiber type variables and sprinting, jumping, strength, power and endurance performances in sprinters and marathon runners. Furthermore, the study explored which muscle fiber type variable influences athletes` performance the most and which variable discriminates sprinters from marathon runners. Body composition, vastus lateralis muscle fiber composition, sprinting, jumping, strength, maximum isometric force, rate of force development and endurance performance were assessed in well-trained sprinters (n = 15; age: 24.7 ± 4.1 years; body mass: 82.7 ± 8.8 kg; body fat: 11.3 ± 4.2%) and marathon runners (n = 15; age: 26.1 ± 3.2 years; body mass: 69.7 ± 4.3 kg; body fat: 9.5 ± 3.3%). Significant correlations were observed between muscle fiber composition variables and performances (r = -0.848 to 0.902; p < 0.05), with percentage cross-sectional areas (%CSAs) showing the strongest associations. Regression analyses confirmed %CSAs as the strongest predictors of performance (R2: 0.796-0.978; p < 0.001; B coefficients: -0.293-0.985), while discriminant analysis accurately differentiated sprinters from marathon runners (100%, p < 0.001) by only using athletes` muscle fibers` %CSAs. In conclusion, muscle fibers` %CSAs may be the most critical variables for explaining and distinguishing sprinters` and marathon runners` performances.